Technologies used by nursing managers in Portuguese hospitals - Maria Manuela Ferreira Pereira da Silva Martins; Letícia de Lima Trindade; Lara Vandresen; Maria José Mesquita Gomes Correia Leite; Carla Marina Gomes Pereira; Maria José Lumini Landeiro (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To analyze the association between the characteristics of nurse managers and the use of information technologies in Portuguese hospitals. Method: A cross-sectional quantitative study involving 138 nurse managers. The managers answered a questionnaire about the use of key information and communication technologies in management. The findings were submitted to descriptive and analytical statistical analysis. Results: Women predominated, with more than 25 years in the profession and more than ten in management. It showed that the managers identify the utility and easiness of a singular way for each technology, the use of which is influenced by the nurses' socio-occupational characteristics, their gender, specialization (having it or not), and the time of experience in services and management being significant. Conclusion: The study contributes to explain and predict the intention to use, as well as the mastery of technologies in hospital management, providing support of choice in the management of services and need for qualification for use.